Perjanjian Jasa Titip (Jastip) Online: Tinjauan Elementer Pemberian Kuasa dan Jual Beli dalam Hukum Perikatan Indonesia - Dinda Delfina; Adinda Dwi Larasat (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
As a Mandate agreement (regulated under Article 1792 et seq. of the Civil Code), the customer often entrusts the Jastip provider with the authority to purchase goods on their behalf. The provider acts as an agent, undertaking an action for and on behalf of the customer, for which they receive a fee or commission. Conversely, the transaction often culminates in a final exchange resembling a Sale and Purchase agreement (regulated under Article 1457 et seq. of the Civil Code), where the provider transfers the purchased goods to the customer for an agreed-upon price, which includes the cost of the item and the service fee. This duality leads to ambiguity concerning the precise rights, obligations, and legal liability of each party, particularly in cases of non-performance (wanprestasi), defects in the product, or losses during transit. The current legal uncertainty necessitates a clear delineation of the underlying contract to ensure legal certainty (kepastian hukum) and consumer protection within this growing sector. The agreement’s validity, like any contract, relies on the fulfillment of the four requirements of a valid contract stipulated in Article 1320 of the Civil Code. Ultimately, this analysis suggests that while the Jastip agreement predominantly functions as a specialized form of Mandate involving intermediary services, its practical execution carries substantial elements of a Sale and Purchase transaction. A clearer legal framework or standardized contractual template is essential to mitigate potential disputes and afford adequate legal protection to both Jastip service providers and consumers in the digital era.